Fate of Bacillus cereus within phagocytic cells - Rolny, Ivanna Sabrina (2017)
In this study we assessed the interaction of different strains of Bacillus cereus with murine peritoneal macrophages and cultured phagocytic cells (Raw 264.7 cells). Association, internalization, intracellular survival, routing of bacteria to different compartments and expression of MHCII were assessed in cells infected with different strains of B. cereus in vegetative form. Association values (adhering + internalized bacteria) and phagocytosis were higher for strain B10502 than those for strains 2 and M2. However, after 90 min interaction, intracellular survival was higher for strain 2 than for strains M2 and B10502. Acquisition of lysosomal markers by B. cereus containing vacuoles (BcCV), assessed by LAMP1 and Lysotracker labelling occurred shortly after internalization. The highest ratio of LAMP1(+)-BcCV was found for strain M2. This strain was able to survive longer than strain B10502 which routes to LAMP1 containing vacuoles to a lesser extent. In addition, strain M2 stimulated expression of MHCII by infected cells. Confocal analyses 60 or 90 min post-infection showed different percentages of co-localization of bacteria with Lysotracker. Results suggest strain-dependent interaction and intracellular killing of B. cereus by phagocytic cells. These findings could be relevant for the pathogenic potential of Bacillus cereus strains.